Development of Power Point Media as an Indonesian Language Learning Media in Elementary Schools - Ajat Sudrajat; Intan Teja Asih; Mustika Nurlaeli; Henny Setiani (Journal of Education Technology Information Social Sciences and Health, 2024)
Limited teaching materials can be a factor inhibiting the teaching and learning process so that learning becomes ineffective. To overcome this, it is necessary to develop learning media. One of the learning media that can handle this is power point. Power point media is an interesting media in terms of presentation. Power point media is a media that was developed as a solution to improve understanding of Indonesian language subjects. Therefore, the author conducted research, this research is seen as development research which aims to develop Power Point learning media as an Indonesian language learning media. The type of research used in this research is a qualitative method.